Exploring Inequality Through Service Learning in Higher Education: A Bibliometric Review Study - Martínez-Heredia, Nazaret; Corral-Robles, Silvia; González-Gijón, Gracia; Sánchez-Martín, Micaela (Frontiers in Psychology, 2022)
Service-learning is an innovative methodology, widely known around the world. The implementation of this methodology involves classroom learning and real practice. It is based on a cooperative methodology, integrating community service and learning in a connected way. Its main strength lies in its great potential as a transformative social movement to reduce inequality. The main aim of this study is to understand and describe the field of service learning and inequality in higher education through a bibliometric analysis. A descriptive, retrospective and cross-sectional methodology is used to describe the information obtained from the 20 references on the topic registered in the Scopus and Web of Science databases using a mixed methodology. The results show that most of the publications are concentrated in 2016, being United States, the country with the largest amount of scientific production on this subject. It is also worth noting the high production since 2012, as well as the increase in the number of countries doing research on this topic.